(untitled) (REMUNOM, 2025)
The purpose of this study was to analyze the impacts of the use of digital technologies on vaccine monitoring, focusing on immunization coverage and nursing practice. Based on an integrative review of the literature, several digital tools used in the vaccination context were identified, including electronic information systems, management platforms, mobile applications, interactive dashboards, SMS text messages, and the use of social media. These technologies are used both for administrative purposes—such as recording, controlling, and monitoring vaccination data—and in educational and communication actions aimed at the population, with the aim of addressing vaccine hesitancy and promoting adherence to immunization campaigns. The analysis of the selected studies allowed the findings to be organized into three main axes: (1) educational and health literacy strategies led by nursing professionals to encourage vaccination; (2) use of information systems and digital tools to improve the monitoring and planning of vaccination actions; and (3) digital interventions and communication resources aimed at expanding vaccination coverage by engaging with the community. It was concluded that the integration of these technologies into nursing practice strengthens immunization management, improves the quality of care provided, and contributes significantly to increasing vaccination coverage. Thus, the conscious and strategic use of digital resources represents a significant advance in the modernization of public health actions, especially with regard to vaccination surveillance and promotion.